Effects of Montmorency tart cherry (Prunus Cerasus L.) consumption on vascular function in men with early hypertension. Issue 6 (4th May 2016) - Keane, Karen M; George, Trevor W; Constantinou, Costas L; Brown, Meghan A; Clifford, Tom; Howatson, Glyn
ABSTRACT: Background: Tart cherries contain numerous polyphenolic compounds that could potentially improve endothelial function and reduce cardiovascular disease risk. Objective: We sought to examine the acute effects of Montmorency tart cherry (MC) juice on vascular function in subjects with early hypertension. Design: A placebo-controlled, blinded, crossover, randomized Latin square design study with a washout period of ≥14 d was conducted. Fifteen men with early hypertension [systolic blood pressure (SBP) ≥130 mm Hg, diastolic blood pressure ≥80 mm Hg, or both] received either a 60-mL dose of MC concentrate or placebo. Microvascular reactivity (laser Doppler imaging with iontophoresis), arterial stiffness (pulse wave velocity and analysis), blood pressure, and phenolic acid absorption were assessed at baseline and at 1, 2, 3, 5, and 8 h postconsumption. Results: MC consumption significantly lowered SBP ( P < 0.05) over a period of 3 h, with peak reductions of mean ± SEM 7 ± 3 mm Hg 2 h after MC consumption relative to the placebo. Improvements in cardiovascular disease risk factors were closely linked to increases in circulating protocatechuic and vanillic acid at 1–2 h. Conclusions: MC intake acutely reduces SBP in men with early hypertension. These benefits may be mechanistically linked to the actions of circulating phenolic acids. This study provides information on a new application of MCs in health maintenance, particularly in positively modulating SBP. This trial was registered at clinicaltrials.gov as NCT02234648.